A Retrospective Evaluation of the Retrosigmoidal Approach for Petroclival Meningioma Surgery and Prognostic Factors Affecting Clinical Outcome - Masalha, Waseem; Heiland, Dieter Henrik; Steiert, Christine; Krueger, Marie T.; Schnell, Daniel; Scheiwe, Christian; Grosu, Anca-L.; Schnell, Oliver; Beck, Juergen; Grauvogel, Juergen (Frontiers in Oncology, 2022)
Introduction Petroclival meningioma (PCM) remains a major neurosurgical challenge. There are still controversial strategic treatment concepts about surgical approach, the extent of resection, and postoperative radiotherapy. We aimed to evaluate prognostic factors influencing the progression-free survival (PFS) rates of PCM, with a particular focus on the retrosigmoidal approach, the role of the extent of resection, and postoperative radiotherapy. Methods Eighty-nine patients with complete follow-up data were included. All patients were operated on via a retrosigmoidal approach, of whom 19 underwent gross total resection (GTR) and 70 underwent subtotal resection (STR). In the subgroups of tumours with infiltration of the cavernous sinus, 41 patients received near total resection (NTR) and 24 STR. Thirty-one patients received postoperative radiotherapy of the residual tumour and 58 were treated with surgery alone. Kaplan-Meier analyses and Cox-regression were used to identify significant factors associated with treatment. Results GTR (p=0.0107) and postoperative radiotherapy (p=0.014) were associated with significantly improved PFS. Even the subgroup analysis of extended PCM with infiltration of the cavernous sinus (CS) showed an advantage for PFS after near total resection (NTR) (p=0.0017). The additional radiotherapy of the residual tumour in the CS in this subgroup also showed a beneficial effect on PFS (p=0.012). Conclusion The extension of surgical resection remains the most important prognostic factor in relation to oncological outcomes. However, the GTR of extended PCM with infiltration of the CS is associated with significant neurological morbidity and requires additional adjuvant therapy concepts. Postoperative radiotherapy is an important element in the treatment of the residual tumour after surgery.